Effect of Competence of Village Government Apparatus and Organizational Commitment on Village Government Performance with Village Financial Management as an Intervening Variable (Case Study in Villages in East Seunagan District, Nagan Raya Regency) - Herliani, Herliani; Sari, Maya; Nurmalasari, Eka (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to examine the effect of competence of village government apparatus and organizational commitment on village government performance with village financial management as an intervening variable, case study in Villages in East Seunagan District, Nagan Raya Regency. The approach in this study is an associative/quantitative approach. The population in this study were Villages in East Seunagan District which consisted of 34 Villages. The sampling technique in this study used the saturated sample technique found in non-probability sampling. The research respondents were 102 people from 34 villages consisting of the Village Head, Secretary and Treasurer. Data was collected using a questionnaire which was delivered directly to the respondents. Data processing is done by structural equation modeling-partial least square (SEM-PLS). The results of this study indicate that competence of the village government apparatus effect village government performance. Organizational commitment effect village government performance. Village financial management effect village government performance. Competence of the village government apparatus effect village financial management. Organizational commitment effect village financial management. Village financial management can mediate effect of competence of the village government apparatus on village government performance. Village financial management can mediate effect of organizational commitment on village government performance.